Diseño de un sistema de compactación de papel y cartón para la empresa Mac Anillados y Acabados Impresos SAS. (2018)
In this project the design of a paper and cardboard compaction system for the company Mac Anillados Y Acabados Impresos SAS. was carried out, it seeking to improve the process of compaction of current waste and make the work easier for the operator, obtaining greater performance and productivity. Initially, an analysis was made of how the paper and cardboard waste collection and compaction process is carried out, taking design alternatives for the operation of the system, which were evaluated to select the alternative that would satisfy the need required by the process. There was obtained precise information of the components of the system, such as dimensions and materials, were obtained to be able to develop manufacturing plans, operation and maintenance manuals, assembly and assembly. Additionally, the viability and financial feasibility of the designed compaction system is found through a study.